Development and Characterization of Prickly Pear Seed Oil Microcapsules in a Biopolymeric Alginate-Gelatin Matrix for Controlled Release - BELLACHE, Rebiha (Biopolymer Applications Journal, 2026)
This study aimed to encapsulate the sensitive bioactive compounds of Prickly Pear Seed Oil (PPSO) (Opuntia ficus-indica) using a biopolymeric matrix composed of sodium alginate and gelatin. PPSO, which is rich in essential fatty acids and antioxidants, is highly susceptible to degradation caused by light, oxygen, and heat. Microcapsules were prepared using the complex coacervation technique to enhance oil stability and ensure controlled release under physiological conditions. The physicochemical, structural, and thermal properties of the microcapsules were evaluated using UV–Visible spectroscopy, FTIR, thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC). The results confirmed successful oil encapsulation and improved thermal stability compared to pure PPSO. The formulation containing 0.75 g of oil exhibited the highest encapsulation efficiency (93.51%) and the most favorable controlled release behavior. Release studies demonstrated low oil release in simulated gastric fluid (pH 1.2), followed by a sustained and controlled release in simulated intestinal media (pH 6.8 and 7.4). These findings highlight the effectiveness of the alginate–gelatin system for stabilizing PPSO, offering promising potential for applications in food, cosmetic, and pharmaceutical industries.<audio class="audio-for-speech"></audio> Translator <audio class="audio-for-speech"></audio> Translator